A novel white-light-emitting conjugated polymer derived from polyfluorene with a hyperbranched structure. (5th May 2015) - Sun, Jing; Yang, Junli; Zhang, Chongyang; Wang, Hua; Li, Jie; Su, Shijian; Xu, Huixia; Zhang, Tiaomei; Wu, Yuling; Wong, Wai-Yeung; Xu, Bingshe
Abstract : A novel white-light hyperbranched conjugated polymer utilizing polyfluorene as the branches and Ir(piq)3 as the cores has been investigated. Abstract : A series of novel hyperbranched conjugated polymers containing red phosphorescent iridium complexes that produce white-light emission have been designed and synthesized. The iridium complexes, tris[1-phenylisoquinolinato- C 2, N ]iridium(iii ) (Ir(piq)3 ), as red emitters, are covalently connected with the polyfluorene segments as blue emitters. Based on the hyperbranched structure, the conjugated polymers with large steric hindrance can effectively suppress the triplet–triplet annihilation. Simultaneously, the synthesized polymers express relatively better thermostability, photophysical properties, with a higher fluorescence quantum yield (57–77%), and electrochemical properties. By incorporating about 0.1 mol% of Ir(piq)3 into the conjugated polymers, the white-light emission could be achieved. Single-active-layer polymer light emitting devices with the configuration of ITO/PEDOT:PSS/polymer/TPBI/LiF/Al have been fabricated. Among all the devices, PF-Ir(piq)3 100 device exhibits a Commission Internationale de l'Eclairage coordinate of (0.30, 0.23), which is close to that of pure white light. This indicates that the hyperbranched polymers exhibiting mixed fluorescence and phosphorescence emission would be promising white-light materials.